2020
DOI: 10.1523/eneuro.0168-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Reelin Counteracts Chondroitin Sulfate Proteoglycan-Mediated Cortical Dendrite Growth Inhibition

Abstract: Disruptions in neuronal dendrite development alter brain circuitry and are associated with debilitating neurological disorders. Nascent apical dendrites of cortical excitatory neurons project into the marginal zone (MZ), a cell-sparse layer characterized by intense chondroitin sulfate proteoglycan (CSPG) expression. Paradoxically, CSPGs are known to broadly inhibit neurite growth and regeneration. This raises the possibility that the growing apical dendrite is Significance Statement Appropriate dendritic devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 83 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…As such, a disruption of PNNs reactivates visual plasticity 51,52 . Importantly, Reelin interacts and co-localizes with both CSPGs and HSPGs, as shown in two recent papers 13,53 . Along this line, an interesting recent study demonstrated a new role for Reelin in modulating cortical plasticity .…”
Section: Reelin Modulates Synaptic Plasticity Learning and Behaviormentioning
confidence: 64%
“…As such, a disruption of PNNs reactivates visual plasticity 51,52 . Importantly, Reelin interacts and co-localizes with both CSPGs and HSPGs, as shown in two recent papers 13,53 . Along this line, an interesting recent study demonstrated a new role for Reelin in modulating cortical plasticity .…”
Section: Reelin Modulates Synaptic Plasticity Learning and Behaviormentioning
confidence: 64%
“…CSPG-PTPRσ binding promotes monomerization of the receptor to increase its dephosphorylation activity, while HSPG-PTPRσ binding promotes clustering of the receptor and a decrease in dephosphorylating activity (Wu et al 2017). In the extracellular matrix milieu, the attention of the growth cone to the ratio of HSPGs to CSPGs as well as other extracellular proteins such as reelin (Zluhan et al 2020) or laminin (McKeon et al 1995) is, therefore, important in determining whether axon outgrowth proceeds. Following SCI, however, approaching axons are strongly inhibited by the preponderance of upregulated CSPGs found radiating from the glial scar (Davies et al 1997).…”
Section: The Lar Family Receptors Mediate the Inhibitory Actions Of Cspgsmentioning
confidence: 99%
“…This also abrogates CS ligand binding to the inhibitory receptor RPTPσ. Thus, PTN increases dendrite regeneration in the adult cerebral cortex and axonal regeneration in the injured adult spinal cord [ 166 ]. PTN also increases neural proliferation and neurite outgrowth in cultured neurons.…”
Section: Cell Surface Receptors That Bind Cs- and Hs-pgs To Regulate Neuritogenesismentioning
confidence: 99%
“…Systemic delivery of a function-blocking peptide has been used to modulate RPTPσ interactions with CS-PGs to promote neuronal recovery following SCI. Inhibition of cortical dendritic growth by CS-PGs, can also be counteracted by reelin signalling [ 166 ]. Reelin is an extracellular signalling protein that regulates the alignment of radial neurons and rescues neurite outgrowth in the presence of CS-PGs.…”
Section: Cell Surface Receptors That Bind Cs- and Hs-pgs To Regulate Neuritogenesismentioning
confidence: 99%